2008
DOI: 10.1510/icvts.2008.187963
|View full text |Cite
|
Sign up to set email alerts
|

Impact of 3-mm Blalock-Taussig shunt in neonates and infants with a functionally single ventricle

Abstract: Functionally single ventricle (f-SV) is susceptible to volume overload. Atrioventricular valve regurgitation (AVVR) tends to develop and ventricular function deteriorates due to excessive pulmonary blood flow following modified Blalock-Taussig shunt (mBTS). On the other hand, a small caliber graft has risks of early obstruction and poor growth of pulmonary vascular beds. We assessed the effect of mBTS with a 3-mm graft to circumvent volume overload in f-SV on achievement of the right heart bypass. Eleven neona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In a study of 3-mm Blalock-Taussig shunts in single-ventricle neonates, Kajihara et al found a late death rate (not specified if related to thrombosis) of 1 in 11 patients studied. 7 The recurrent nature of thrombosis in our patient was unusual in our experience and is what led us to investigate for other causes. We believe the low antithrombin levels, while not the sole factor (small infant, small shunt, surgical trauma, hypoxia, and rapid fluid shifts), increased the likelihood of thrombosis.…”
Section: Discussionmentioning
confidence: 59%
“…In a study of 3-mm Blalock-Taussig shunts in single-ventricle neonates, Kajihara et al found a late death rate (not specified if related to thrombosis) of 1 in 11 patients studied. 7 The recurrent nature of thrombosis in our patient was unusual in our experience and is what led us to investigate for other causes. We believe the low antithrombin levels, while not the sole factor (small infant, small shunt, surgical trauma, hypoxia, and rapid fluid shifts), increased the likelihood of thrombosis.…”
Section: Discussionmentioning
confidence: 59%
“…There have been a limited number of reports on small shunts (3.0-mm graft); thus, the feasibility of these small shunts has not been widely investigated. 21) In the present series, we reduced the graft size to prevent excessive pulmonary blood flow and cardiogenic shock. A possible disadvantage of small grafts is shunt occlusion; therefore, in the operative procedure, we placed a BTS at the proximal portion of the brachiocephalic and pulmonary arteries with sufficient anastomosis size, and the median sternotomy approach was selected for all patients.…”
Section: Discussionmentioning
confidence: 95%